Increasing myopic refraction reduces random dot stereopsis in Chinese myopic patients: a cross-sectional study - Xin Xiao; Xiyang Yang; Yan Luo; Lili Li; Enwei Lin; Min Kong; Qi Chen; Jin Zeng; Li Yan; Wuqiang Luo (BMC Ophthalmology)
Abstract Objective To investigate the effects of myopic spherical equivalent (SE) on random dot stereopsis and influencing factors in Chinese adults with myopia. Methods A cross-sectional design was employed, and 988 Chinese myopic individuals (520 [52.6%] females) aged 18.0–48.7 years were recruited from the People’s Hospital of Guangxi. The participants underwent assessments for visual acuity, myopic SE, random dot stereopsis at 0.8 m (RDS0.8) and at 1.5 m (RDS1.5) and binocular function parameters (such as perceptual eye position (PEP), fixational eye movement, and the signal‒noise ratio (SNR)). The data were analysed via Pearson or Spearman correlations and multivariate logistic regression. Results Among the 988 participants, only 53 (5.4%) presented with abnormal RDS0.8, and 834 (84.4%) presented with abnormal RDS1.5. A significant association was found between SE and the prevalence of abnormal RDS1.5 (OR: 1.14, 95% CI: 1.03–1.26; P = 0.014) after adjusting for covariates. High myopia was more strongly associated with abnormal RDS1.5 than mild myopia was in the unadjusted model (OR: 1.85, 95% CI: 1.03–3.26; P = 0.037). Subgroup analyses revealed that the associations between SE and abnormal RDS1.5 were stronger among females, individuals aged > 25 years, those with normal fixational eye movement, and those with abnormal SNRs. Only vertical PEP (target 1°) was significantly associated with myopic group and abnormal RDS0.8, whereas vertical PEP (target 3°), horizontal PEP (target 1°), and vertical PEP (target 1°) were significantly associated with abnormal RDS1.5. Conclusions Myopic SE was associated with the prevalence of abnormal random dot stereopsis at 1.5 m in myopic patients, indicating that increasing myopic SE may impair distance random dot stereopsis in this population. Clinical trial number Not applicable.